PENGEMBANGAN MEDIA SCRAPBOOK BERBASIS INQUIRY PADA MATERI FLORA DAN FAUNA DI KELAS IV SD - Devita Yetti Manik; Sukmawarti (STKIP Subang, 2023)
Motivated by the learning media used in the science learning process, especially on Flora and Fauna material, still using printed teaching materials, teaching staff still using the lecture method, lack of students' understanding of flora material. and fauna, decreased interest and motivation for learning, and a lack of use of learning media in the classroom. This researcher aims to design inquiry-based scrapbook media on class IV elementary school flora and fauna material and to determine the feasibility of developing inquiry-based scrapbook media on class IV flora and fauna material SD. Product development in this research uses the ADDIE development model. This method and model was chosen because it aims to produce an inquiry-based scrapbook media product on flora and fauna material in class IV elementary school. The subject of the trial was a class IV teacher at UPT SD Negeri 104211 Marindal with material on flora and fauna. The object of this research was inquiry-based scrapbook media. This research uses a questionnaire as a tool to test the feasibility of inquiry-based scrapbook media through validation by media experts, material experts, teacher responses and student responses. Qualitative data is obtained from the formula used to determine the suitability of media and materials. The data obtained is used as a reference for making revisions to the products being developed. Based on the calculations above, the results of the overall assessment of the material experts reached the instrument used to collect data, namely a questionnaire. The validation results for inquiry-based scrapbook media were media expert validation obtained 76% with appropriate criteria, material expert validation obtained a score of 76% with suitable criteria for use, teacher response obtained a score of 92.5% with very suitable criteria for use and student responses obtained a score of 93.3 % with criteria that are very suitable for use. Based on the data obtained, it can be concluded that inquiry-based scrapbook media can improve learning outcomes for fourth grade elementary school students. Can improve class IV learning outcomes at UPT SD Negeri 104211 Marindal 4.